The problem of labour in fourteenth-century England - Bothwell, James; Goldberg, P. J. P., 1958-; Ormrod, W. M., 1957- (York Medieval Press in association with the Boydell Press, 2000)
Labour was one of the central issues in public and political discourse during the fourteenth century. The natural disasters and profound social changes of the period created not merely a 'problem' of labour, but also new ways of discussing and (supposedly) solving that problem.